(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Skin problems known as hyperkeratotic diseases are characterized by red, dry, cracked, and scaling skin, and they can be treated by using salicylic acid through topical application. The purpose of this study is to create and characterize a salicylic acid film-forming of hydrophilic polymers for the treatment of hyperkeratotic and scaling disorders that have wipe-off resistance, longer retention at the treatment site and is simple to spread and apply to the skin in to overcome the disadvantages of conventional topical formulation. The film-forming gel is prepared with HPMC E15, Carbopol 934, propylene glycol, water, ethanol, and the drug. It is then optimized using 22 factorial designs and is characterized by its physical characteristics, pH level, spreadability, drug content, rheological study, in vitro drug release, drying time, mechanical properties of the film, and other factors. Salicylic acid film-forming gel stability, skin irritancy, ex-vivo permeation, and skin retention were also investigated. For certain tests, every formulation produces the expected results. The optimization analysis found that viscosity increases and drug release decrease when HPMC E15 and Carbopol 934 concentrations rise. The improved formulation had a viscosity of 47.6 ± 1.23 cp and a 90.23 ± 2.01% drug release. It is concluded that salicylic acid film-forming gel is efficiently produced with hydrophilic polymers and creates thin, protective, emollient, and water-soluble film to treat hyperkeratotic and scaling diseases.